Mechanism of interaction influence between sedimentation and diagenesis on quality of shale oil generation and storage: A case study of Paleogene shale of Shahejie Formation in Niuzhuang Subsag of Dongying Sag - TENG Jianbin (Youqi dizhi yu caishoulu)
The shale oil in the Lower Es3 and Upper Es4 Submembers of Niuzhuang Subsag of Dongying Sag is rich， with high yield， belonging to the typical terrestrial shale oil. Currently， the understanding of material exchanges and reservoir characteristics driven by diagenesis between shale laminae is not clear. The mechanism of the interaction influence of sedimentation and diagenesis on the quality of shale oil generation and storage was analyzed by the petrology， geochemical analysis of trace elements and rare earth elements， and other methods based on the sparry calcite veins and material transfer phenomena， as well as shale hydrocarbon generation and oil-bearing parameters. In addition， material transfer between shale laminae， generation of sparry calcite veins， and shale oil migration were scientifically explained. The geochemical microanalysis of rare earth elements reveals that the Th and U element contents within different material laminae in descending order are as follows： argillaceous layer， sparry calcite vein， recrystallized calcite layer， and contact surface between argillaceous layer and sparry calcite vein. The differentiation of light and heavy rare earth elements in the argillaceous layer and sparry calcite vein is obvious， showing significant enrichment of light rare earth elements and loss of heavy rare earth elements， exhibiting obvious negative anomalies of Dy. The differentiation of light and heavy rare earth elements in the recrystallized calcite layer is not obvious， showing a negative anomaly of Dy. The contents of Th， U， and rare earth elements in the sparry calcite veins are lower than those in the argillaceous layer and higher than those in the recrystallized calcite layer， and it is an essential geochemical indicator to distinguish between the sparry calcite veins and the recrystallized calcite layer. The compaction effect and material component content are the main factors affecting shale porosity. According to the nuclear magnetic resonance experiment， the reduction in pore size greater than 30 nm is the most significant in shale with a burial depth of 3 300-3 600 m， and the reduction amplitude is about 1%/hm. The total content of terrestrial minerals is positively correlated with porosity due to the effect of overpressure fluid pore retention caused by hydrocarbon pressurization. Hydrogenated carbonate minerals have strong resistance to overlying rock pressure， which is beneficial for artificial fracturing. Their intergranular and dissolution pores have large sizes with superior oil storage capacity.